Knowledge, attitude, practice, and self-efficacy of women regarding cervical cancer screening - Shahnaz Ghalavandi; Alireza Heidarnia; Fatemeh Zarei; Reza Beiranvand (Korean Society of Obstetrics and Gynecology, 2021)
Objective Iran has a low incidence of cervical cancer (CC). The country is introducing an organized screening system, including human papillomavirus screening. Studies show a high dropout rate among eligible women in continuing testing. Methods This descriptive-analytic study was part of the first phase of a clinical trial conducted on a random sample of 400 women aged 18-49 in Andimeshk City, Khuzestan Province, in 2020. The data collection tool consisted of a man-made questionnaire that included domains of demographic characteristics, knowledge, attitude, practice, and self-efficacy in the Pap smear test. The data were analyzed with Stata-16 using linear and logistic regression models. Results The mean knowledge, attitude, and self-efficacy scores were 6.80±2.33, 34.99±4.32, and 28.67±7.34, respectively. In the multiple models, every unit increase in the knowledge or attitude scores raised the mean self-efficacy score by 1.04 and 0.48, respectively (P<0.001). Every unit increase in the knowledge and self-efficacy scores increased the chance of performing Pap smear 1.61 and 1.41 times, respectively (P<0.001). Conclusion Given the association of women's knowledge and self-efficacy with practice in performing the Pap smear, it seems that an effective program promoting women's health behavior regarding CC screening would include applied education to raise community awareness and improve women's attitudes, self-efficacy, and practice.